PERSEPSI SISWA TERHADAP KOMPETENSI PEDAGOGIK GURU PENJASORKES - Idrus Afandi; Riswanti Rini; Ade Jubaedi (JUPE (Jurnal Penjaskesrek), 2014)
The objective of this study was to determine the students 'perceptions toward pedagogical competence of Physical Education Sport, and health teachers' so that it would become a benchmark in providing better teaching-learning process. The research method used in this study is descriptive analysis with total sample of 213 people by a sampling of the whole population developed by Isaac and Michael. This technique has tables’ error rate 1%, 5%, and 10 %. The researcher used questionnaire. He analyzed data by using Likert scale. The results obtained in the research of students 'perceptions of pedagogical competence of physic is considered good to fairly well by the overall students’ percentage stated strongly agree is amount to 26.85%, while the students stated agree is amount to 57.75%.Tujuan penelitian ini untuk mengetahui persepsi siswa terhadap kompetensi pedagogik guru penjasorkes agar menjadi panduan guru pejasorkes dalam memberikan pembelajaran lebih baik. Metode yang digunakan adalah metode deskriptif, dengan jumlah sampel sebanyak 213 orang menggunakan teknik pengambilan sampel yang dikembangkan oleh Issac dan Michael dengan tabel tingkat kesalahan 1%, 5%, dan 10%. untuk tehnik pengambilan data menggunakan tekhnik angket. Analisis data menggunakan skala Likert. Hasil yang diperoleh menunjukan bahwa persepsi siswa terhadap kompetensi pedagogik guru penjasorkes cukup baik dengan pesentase keseluruhan menyatakan sangat setuju ada 26,85%, menyatakan setuju ada 57,75%.Kata kunci: guru penjasorkes, kompetensi pedagogik, metode diskriptif